Characterization of atrazine induced protein adducts - Dooley, Gregory, author; Tessari, John D., advisor (Colorado State University. Libraries, 2007)
Atrazine (2-chloro-4-ethylamino-6-isopropylamino-s-triazine) (ATRA) is the most commonly applied herbicide in the U.S. and is frequently detected in drinking water at significant levels. ATRA metabolism yields diaminochlorotriazine (DACT), an electrophilic molecule that can react with nucleophilic protein residues forming a covalent adduct. We first demonstrated this interaction with hemoglobin from rats exposed to 30-300 mg/kg ATRA. Mass spectrometry (MS) analysis of hemoglobin tryptic digests indicated a 110 Da adduct on Cys-125 of the β-subunit. Based on in vitro incubations of 90 ug/ml DACT and hemoglobin yielding the identical adduct observed with in vivo ATRA exposures, adduct formation was by a nucleophilic substitution reaction between DACT and Cys-125. Albumin was then investigated since it contains an exposed Cys-34 that could be targeted by DACT. Again using MS, a 110 Da adduct was located on Cys-34 of albumin from rats exposed to 20-200 mg/kg ATRA and rat and human albumin exposed in vitro to 90 ug/ml DACT. Immunochemical detection using a DACT adduct antibody also detected the adduct in albumin samples from rats given 5-200 mg/kg ATRA and rat and human albumin exposed in vitro to DACT. No adducts were detected in control animals or in the in vitro controls with this method. These data support a novel immunochemical detection system that could provide a rapid screening methodology for the detection of ATRA in exposed human populations. Finally, we used the DACT antibody to located modified proteins in the pituitaries of ATRA exposed rats and DACT exposed LβT2 rat pituitary cells. Since ATRA exposure suppresses the luteinizing Hormone (LH) surge, protein adducts in the pituitary may be involved in this mechanism of action. 2DE followed by Western blotting showed numerous spots (>30) that were not present in control from both exposed rats and LβT2 cells. Using MS analysis of matched protein spots, 8 unique proteins in the rats and 19 unique proteins in LβT2 cells were identified. Each of these proteins contained solvent exposed cysteine residues, making them targets for DACT. Future research will be necessary to elucidate the functional role of these adduct and their involvement in ATRA/DACT induced LH suppression.
Keywords: atrazine; biomarkers; protein adducts; toxicology